2019
DOI: 10.1093/mnras/stz2410
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on high-J CO emission lines in z ∼ 6 quasars

Abstract: We present Atacama Large Millimiter/submillimiter Array (ALMA) observations of eight highly excited CO (J up > 8) lines and continuum emission in two z ∼ 6 quasars: SDSS J231038.88+185519.7 (hereafter J2310), for which CO(8-7), CO(9-8), and CO(17-16) lines have been observed, and ULAS J131911.29+095951.4 (J1319), observed in the CO(14-13), CO(17-16) and CO(19-18) lines. The continuum emission of both quasars arises from a compact region (< 0.9 kpc). By assuming a modified black-body law, we estimate dust masse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 87 publications
(164 reference statements)
0
30
0
Order By: Relevance
“…We have also estimated the extent of the FIR line emission by performing a 2D-Gaussian fitting of the [CII] flux map with the CASA task imfit. In addition to the image plane analysis, we have also performed the size measurements on the uv plane by collapsing the spectral channels around the line peak and following the procedure explained in (Carniani et al 2019), which adopts the GALARIO package Tazzari et al (2018). The two measurements are in agreement within the errors.…”
Section: Observations and Data Analysismentioning
confidence: 99%
“…We have also estimated the extent of the FIR line emission by performing a 2D-Gaussian fitting of the [CII] flux map with the CASA task imfit. In addition to the image plane analysis, we have also performed the size measurements on the uv plane by collapsing the spectral channels around the line peak and following the procedure explained in (Carniani et al 2019), which adopts the GALARIO package Tazzari et al (2018). The two measurements are in agreement within the errors.…”
Section: Observations and Data Analysismentioning
confidence: 99%
“…Error bars are estimated by propagating the error of the line flux on L CO , and assuming a variation of 0.5 dex for L FIR . Also shown are the values obtained for high-redshift SMGs/quasi-stellar objects (QSOs) as the green and grey filled circles in case of CO(9−8) and CO(10−9) transitions, respectively(Carilli & Walter 2013;ALMA Partnership et al 2015;Carniani et al 2019). Right-hand panel: [C II] as a function of FIR luminosity for several kinds of objects at different redshifts.…”
mentioning
confidence: 99%
“…This model also assumes no contributions from separate MIR (e.g., Casey 2012), radio (e.g., Yun & Carilli 2002), or higher frequency (e.g., Leitherer et al 1999) components. In particular, some studies have found that the addition of a MIR power law to a MBB results in a better fit to the FIR SEDs of some galaxies (e.g., Ibar et al 2015;Faisst et al 2020;Reuter et al 2020) Even though the MBB function is indeed simple, it has been found to fit dust SEDs very well (e.g., Bianchi 2013;Jiménez-Andrade et al 2018;Carniani et al 2019;Crocker et al 2019;Lamperti et al 2019). The frequency domain of our model is also controlled to ensure that the contributions from higher and lower frequency components are negligible.…”
Section: Discussion Of Uncertaintiesmentioning
confidence: 99%
“…Optical Thickness: As discussed in Section 4.1.1, we make no assumption on the optical thickness of our source, and therefore use a generalized MBB (similar to e.g., Leech et al 2001;Cortzen et al 2020), rather than one that assumes τ ν << 1 (e.g., Carniani et al 2019;Lamperti et al 2019;Valentino et al 2020). To test whether this source is optically thin, we apply equation 2 to the data in Table 1, using our best-fit dust mass and emissivity index.…”
Section: Discussion Of Uncertaintiesmentioning
confidence: 99%
See 1 more Smart Citation